Effects of Image-Based Rendering and Reconstruction on Game Developers Efficiency, Game Performance, and Gaming Experience - Raptis, George E.; Katsini, Christina; Fidas, Christos; Avouris, Nikolaos (Human-Computer Interaction - INTERACT 2017, 2017)
Image-based rendering and reconstruction (IBR) approaches minimize time and costs to develop video-game assets, aiming to assist small game studios and indie game developers survive in the competitive video-game industry. To further investigate the interplay of IBR on developers’ efficiency, game performance, and players’ gaming experience we conducted two evaluation studies: a comparative, ecologically valid study with professional game developers who created games with and without an IBR-based game development pipeline, and a user study, based on eye-tracking and A/B testing, with gamers who played the developed games. The analysis of the results indicates that IBR tools provide a credible solution for creating low cost video game assets in short time, sacrificing game performance though. From a player’s perspective, we note that the IBR approach influenced players’ preference and gaming experience within contexts of varying levels of player’s visual intersections related to the IBR-created game assets.
Keywords: Evaluation study; Game development efficiency; Game performance; Gaming experience; Image-based rendering and reconstruction; Video games